Trusted Language Runtime (TLR): Enabling Trusted Applications on Smartphones - Santos, Nuno; Raj, Himanshu; Saroiu, Stefan; Wolman, Alec (HotMobile '11 Proceedings of the 12th Workshop on Mobile Computing Systems and Applications, 2011)
Despite their popularity, today's smartphones do not yet offer environments for building and running trusted applications. At the same time, current systems designed for traditional desktop or server machines to enable trusted applications are either too heavyweight for smartphones or too difficult to program. This paper presents the Trusted Language Runtime (TLR), a system for developing and running trusted applications on a smartphone. The TLR is lightweight because 1) it makes use of ARM TrustZone, hardware support that offers rich trusted computing primitives, and 2) it leverages the .NET MicroFramework, a language runtime for embedded and resource-constrained devices. The TLR is easy to program because .NET offers the productivity benefits of modern high-level languages, such as strong typing and garbage collection, to application developers.